A conclusão da obra lucana: um estudo exegético-teológico de At 28,16-28 - Anselmo Júnior, Guilherme Pereira (2015)
The whole set of the texts in the book of the Gospel of Jesus Christ according to Luke (Luke) and the book of Acts of the Apostles (Acts) creates the Lukan work. Its primary recipients, in the second half of the first century AD, are Hellenistic Gentiles who joined the announcement that the hope of ancient Israel takes place in the Messiah Jesus of Nazareth, the Christian kerygma. This religious expression (the Early Christianity) is inserted into an existing tradition, Judaism. Such expression needs to be continued, to provide a self-comprehension and to be based on the roots of that tradition. Otherwise, it would face the risk of provoking a definitive break that would imply a spare expression and without support for both Jews and Gentiles who chose Christianity. This research aims to present the final text of Lukan work, the pericope of Acts 28:16-28, as a summary, climax and paradigm of the confirmation of continuity and completeness of Israel's hopes in the Christian kerygma. Paul, the character, a Hellenistic Jew, apostle of the Gentiles, becomes the protagonist of this process. Therefore, the book of the Acts of the Apostles not only proposes his innocence from the charges, made by the Jewish leaders, as well as it presents him as an imitator of his master, Jesus, and model for other Christians, especially concerning to the reasons given in the Jewish tradition, to the freedom as for the practice on Mosaic usages and laws and to the vocational openness for the announcement to all nations. Thus, this research accesses the Greek text, analyzes it in several instances, translates it into Portuguese and presents an exegetical-theological study of the pericope